Glucose-6-phosphate dehydrogenase deficiency - Leopold, Jane (Henry Stewart Talks, 2007)
G6PD and X-chromosome, Genetics, Protein structure and function, G6PD and neutrophil function/inflammation, Role of G6PD in diabetes mellitus, Hypertension, G6PD modulates vascular oxidant stress, Angiogenesis is regulated by G6PD activity, G6PD and vascular reactivity, G6PD, cardiomyocytes and ischemia-reperfusion